2021
DOI: 10.46347/jmsh.2021.v07i01.012
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study on the Prevalence of Dry Eyes in Type 2 Diabetes Mellitus Patients and its Relation to the Duration and Severity of Disease

Abstract: An Observational Study on the Prevalence of Dry Eyes in Type 2 Diabetes Mellitus Patients and its Relation to the Duration and Severity of Disease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 11 publications
3
7
0
Order By: Relevance
“…Some amount of dryness was present in 34 subjects (68%). Similar observations were present in studies done by Sarkar et al [ 14 ], Wasir et al [ 22 ], and Kamel et al [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Some amount of dryness was present in 34 subjects (68%). Similar observations were present in studies done by Sarkar et al [ 14 ], Wasir et al [ 22 ], and Kamel et al [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…Khetwani et al reported that 148 of their 182 patients were aged >50 years [ 13 ]. Similarly, Sarkar et al reported the mean age of patients was 54 ± 10.06 years with 43% aged between 40 and 50 years [ 14 ]. Acharlu et al demonstrated that the mean age of patients with DM was 55.06 ± 9.70 (range 40-75) years [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the prevalence of dry eye in patients of type 2 DM reported from previous studies is 18%–70%. [ 14 - 21 ] The prevalence of DED in the current study (43.81%) was comparable to a hospital-based study by Sarkar et al . [ 14 ] reporting 42% and by Dutta et al .…”
Section: Discussionsupporting
confidence: 86%